2020
DOI: 10.1111/aor.13789
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics inside the neo‐ and native sinus after TAVR: Effects of implant depth and cardiac output on flow field and coronary flow

Abstract: Abstr act Transcatheter aortic valve replacement (TAVR) has emerged as a widely used therapy for aortic valve diseases. With TAVR, flow hemodynamics may change leading to areas of flow stagnation prone to thrombosis risk. The neo‐sinus, created by introducing a prosthesis inside the diseased native valve, may prompt leaflet thrombosis due to areas of flow stasis. This study attempted to understand the effect of different prosthesis implant depths on the flow field within the neo‐ and native sinus and on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Inadequate coronary flowrate and coronary hypoperfusion could lead to exacerbated heart failure 83 . It has been shown that the TAVR deployment characteristics (such as implant depth, angle and PVL) could affect the coronary flow 83 86 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate coronary flowrate and coronary hypoperfusion could lead to exacerbated heart failure 83 . It has been shown that the TAVR deployment characteristics (such as implant depth, angle and PVL) could affect the coronary flow 83 86 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our results showed that NCC neo-sinus could be influenced the most by PVL, however, the LCC and RCC neo-sinuses irregular washout amplification depends on the severity of PVL and its location. The inefficient sinus and neo-sinus washout favors the thrombotic events after TAVR 86 , 100 .…”
Section: Discussionmentioning
confidence: 99%
“…While distinct, both processes are thought to be sequelae from impaired perfusion or flow to the coronary sinuses ( 17 21 ). The shorter or more compact sinus of valsalva, following valve deployment, promotes flow stagnation and subsequent platelet aggregation leading to atherothrombosis in the coronary vessel or bioprosthetic valve ( 22 , 23 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The haemodynamic metrics such as flow stasis within the neo-sinus has been observed to be dependent on the volumetric size of the neo-sinus [37], cardiac output [38] and heart rate [38]. The volumetric size of the neo-sinus is dependent on the TAV design and implantation parameters royalsocietypublishing.org/journal/rsif J. R. Soc.…”
Section: Haemodynamicsmentioning
confidence: 99%
“…For an intra-annularly positioned valve subjected to similar coronary flow conditions, the resulting increase in velocity magnitude is less apparent. Another study investigated the influence of cardiac output and heart rate in the presence of coronary flow but did not investigate it in the absence of coronary flow for comparison [38]. These authors reported that a lower implant depth and a lower cardiac output led to better native sinus washout but worsened the neo-sinus washout.…”
Section: Influence Of Coronary Flowmentioning
confidence: 99%